Relationship Between Eating Patterns, Physical Activity, and Obesity Incidence Among Madrasah Tsanawiyah (MTs) Students - Damayanti, Dwi Santy; Humairah, Aqiilah Tun; Darmayanti, Firdha; Isnaenil M, Ince Putri; Maarif, Rahmadil (Media Publikasi Cendekia Indonesia, 2024)
Obesity is a chronic disease characterized by excess body fat, increasing the risk of type 2 diabetes, heart disease, bone disorders, reproductive issues, and cancer, while also affecting quality of life, including sleep and mobility. According to WHO, the prevalence of overweight children and adolescents aged 5–19 years increased from 8% in 1990 to 20% in 2022. Recent data from the Ministry of Health in 2023 shows a high prevalence of central obesity among those aged 15–24 years, with 8.3-9.2% in males and 23.4-24.7% in females. This quantitative research employs an observational analytic design with a cross-sectional approach, using SPSS with the Chi-Square test to identify the relationship between dietary patterns and physical activity with the incidence of obesity among MTS students in Gowa Regency. Results indicate no significant relationship between dietary patterns (FFQ and IDDS) and obesity incidence, with p-values of 0.895 and 0.066, respectively. Similarly, physical activity showed no significant relationship with BMI, with a p-value of 0.056. Future studies should consider expanding variables to include factors influencing students' dietary patterns and physical activity, and conduct in-depth analyses using multiple regression.